Terminal uridylyl transferase mediated site-directed access to clickable chromatin employing CRISPR-dCas9 - George, Jerrin Thomas; Azhar, Mohd; Aich, Meghali; Sinha, Dipanjali; Ambi, Uddhav B.; Maiti, Souvik; Chakraborty, Debojyoti; Srivatsan, Seergazhi G. (Journal of the American Chemical Society, 2020)
Locus-specific interrogation of target genes employing functional probes such as proteins and small molecules is paramount in decoding the molecular basis of gene function and designing tools to modulate its downstream effects. In this context, CRISPR-based gene editing and targeting technologies have proved tremendously useful, as they can be programmed to target any gene of interest by simply changing the sequence of the single guide RNA (sgRNA). Although these technologies are widely utilized in recruiting genetically encoded functional proteins, display of small molecules using CRISPR system is not well developed due to the lack of adequate techniques. Here, we have devised an innovative technology called sgRNA-Click (sgR-CLK) that harnesses the power of bioorthogonal click chemistry for remodeling guide RNA to display synthetic molecules on target genes. sgR-CLK employs a novel posttranscriptional chemoenzymatic labeling platform wherein a terminal uridylyl transferase (TUTase) was repurposed to generate clickable sgRNA of choice by site-specific tailoring of multiple azide-modified nucleotide analogues at the 3' end. The presence of a minimally invasive azide handle assured that the sgRNAs are indeed functional. Notably, an azide-tailed sgRNA targeting the telomeric repeat served as a Trojan horse on the CRISPR-dCas9 system to guide synthetic tags (biotin) site-specifically on chromatin employing copper-catalyzed or strain-promoted click reactions. Taken together, sgR-CLK presents a significant advancement on the utility of bioorthogonal chemistry, TUTase, and the CRISPR toolbox, which could offer a simplified solution for site-directed display of small molecule probes and diagnostic tools on target genes.